Association between interpregnancy interval and pregnancy complications by history of complications: a population-based cohort study - Annette K Regan; Gavin F Pereira; Gizachew Assefa Tessema; Amanuel Tesfay Gebremedhin (BMJ Open, 2021)
Objective To examine if the association between interpregnancy interval (IPI) and pregnancy complications varies by the presence or absence of previous complications.Design and setting Population-based longitudinally linked cohort study in Western Australia (WA).Participants Mothers who had their first two (n=252 368) and three (n=96 315) consecutive singleton births in WA between 1980 and 2015.Outcome measures We estimated absolute risks (AR) of preeclampsia (PE) and gestational diabetes (GDM) for 3–60 months of IPI according to history of each outcome. We modelled IPI using restricted cubic splines and reported adjusted relative risk (RRs) with 95% CI at 3, 6, 12, 24, 36, 48 and 60 months, with 18 months as reference.Results Risks of PE and GDM were 9.5%, 2.6% in first pregnancies, with recurrence rates of 19.3% and 41.5% in second pregnancy for PE and GDM, respectively. The AR of GDM ranged from 30% to 43% across the IPI range for mothers with previous GDM compared with 2%–8% for mothers without previous GDM. For mothers with no previous PE, greater risks were observed for IPIs at 3 months (RR 1.24, 95% CI 1.07 to 1.43) and 60 months (RR 1.40, 95% CI 1.29 to 1.53) compared with 18 months. There was insufficient evidence for increased risk of PE at shorter IPIs of <18 months for mothers with previous PE. Shorter IPIs of <18 months were associated with lower risk than at IPIs of 18 months for mothers with no previous GDM.Conclusions The associations between IPIs and risk of PE or GDM on subsequent pregnancies are modified by previous experience with these conditions. Mothers with previous complications had higher absolute, but lower RRs than mothers with no previous complications. However, IPI remains a potentially modifiable risk factor for mothers with previous complicated pregnancies.